Diesel Emissions Control Strategies For The Use Of Diesel Engines In Underground Coal Mines – Preprint 97-144 - N. Paas (Society for Mining, Metallurgy & Exploration, 1997)
Diesel powered equipment has been operated in underground coal fir mare than 50 years. According to the Mine Safety and Health Administration (MSHA), there are approximately 3,000 diesel units operating in underground coal mines in the United States. This number is expected to reach 5,000 diesel units in 250 coal mines by the year 2000. Also, there are approximately 5,000 diesel units operating in metal/nonmetal mines such as trine, potash and salt mines: and more than 3,000 diesel units operating in Canada. This increased popularity of diesel powered equipment over trolley wire, electric trailing cable or battery powered equipment is because of improved safety, greater mobility, higher productivity and increased power of diesel equipment. The operation if diesel powered equipment is not without challenges. Diesel engines generate exhaust emissions, in particular carbon monoxide, oxides of nitrogen, sulfur dioxide, unburned hydrocarbons, and diesel particulate matter that must be maintained at safe levels. The chief method to control ambient exposure has been dilution by ventilation. A new concept to ensure continued safe ambient emissions levels from diesel equipment in underground mines is the EMISSIONS MANAGEMENT PROGRAM™. The program encompasses all factors that will influence diesel emissions. By ESTABLISHING low tailpipe emissions through technology, such as clean engines, clean fuel selection, exhaust aftertreatment devices and filtration of the exhaust gases via the Dry System ™, this program ensures that the baseline emissions are at their lowest technically feasible concentrations. The DST Dry System™ exhaust conditioner reduces DPM by over 98%, as demonstrated through laboratory research at the West Virginia University. Carbon monoxide and hydrocarbon emissions and odor are similarly reduced. MAINTAINING these low emissions requires an expanded training program for operators and mechanics, onboard feed-back devices and a maintenance program with special focus on events and faults that can alter emissions. Finally, an on-board emissions sampling system allows the mechanic to VERIFY emissions levels and help diagnose engine faults. If the tailpipe emissions fall outside an established limit for a particular equipment, corrective actions will be initiated.